ACTR-53. MGMT PROMOTER METHYLATION ANALYSIS FOR ALLOCATING COMBINED CCNU/TMZ CHEMOTHERAPY: LESSONS LEARNED FROM THE CeTeG/NOA-09 TRIAL. (11th November 2019) - Tzaridis, Theophilos; Schäfer, Niklas; Weller, Johannes; Steinbach, Joachim; Seidel, Sabine; Schlegel, Uwe; Sabel, Michael; Hau, Peter; Seidel, Clemens; Krex, Dietmar; Goldbrunner, Roland; Tonn, Joerg-Christian; et al.
Abstract: BACKGROUND: The CeTeG/NOA-09 trial recently showed a survival benefit for combination chemotherapy with CCNU/TMZ in glioblastoma patients with a methylated MGMT promoter as determined by quantitative Methylation-Specific PCR (qMSP). Identifying patient subgroups with a pronounced benefit from this novel treatment is crucial. Here, we report on the prognostic and predictive value of MGMT promoter methylation ratio determined by qMSP and investigate the concordance of pyrosequencing (PSQ) and qMSP for patients in this trial. METHODS: qMSP and PSQ were used for MGMT promoter methylation analysis. The mITT population of the CeTeG/NOA-09 trial was used for multivariate analysis including the parameters MGMT promoter methylation ratio, RPA class and study center. RESULTS: Patients of the mITT population of the CeTeG/NOA-09 trial (n=129) with MGMT promoter methylation ratio greater than 4 (qMSP) showed a superior overall survival compared to patients with borderline methylation ratio of 2–4 (p=0.0251). In the latter patients, treatment with CCNU/TMZ did not show a survival benefit (p=0.924). Multivariate analysis with treatment arm, RPA class and study center as covariates did not confirm a prognostic or predictive value of MGMT promoter methylation ratio (qMSP) for patients of the mITT population (n=129, HR=0.88; 95% CI: 0.72 – 1.08) or patients with a ratio greater than 4 (n=117, HR =0.86; 95% CI: 0.69 – 1.07). In a subset of 49 trial patients, qMSP and PSQ showed not only a high qualitative (45/49; 91.8%), but also a high quantitative concordance rate (Spearman correlation, r=0.83, p< 0.0001). CONCLUSION: Glioblastoma patients with borderline MGMT promoter methylation (qMSP ratio 2–4) do not seem to benefit from combination treatment with CCNU/TMZ. Thus, we propose a qMSP cut-off of 4 as a novel decision tool for clinicians. qMSP and PSQ show a high concordance rate indicating that a decision for combination therapy can also be based on PSQ results.